2024
DOI: 10.3390/biology13050326
|View full text |Cite
|
Sign up to set email alerts
|

Symphonies of Growth: Unveiling the Impact of Sound Waves on Plant Physiology and Productivity

Mario Pagano,
Sonia Del Prete

Abstract: The application of sound wave technology to different plant species has revealed that variations in the Hz, sound pressure intensity, treatment duration, and type of setup of the sound source significantly impact the plant performance. A study conducted on cotton plants treated with Plant Acoustic Frequency Technology (PAFT) highlighted improvements across various growth metrics. In particular, the treated samples showed increases in the height, size of the fourth expanded leaf from the final one, count of bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Several studies have suggested that the response to sound stimulation is complex, further confirming that cell types other than auditory cells can react directly to sound stimuli. For example, it has been shown that sound wave stimulation brings about significant changes to the protein structure of tobacco cells, producing an increase in the alpha helix structure and a decrease in the unwound β helix [62]; furthermore, sound stimulation has produced effects on the cell cycle and on the growth of plants [63,64]. It has been demonstrated that bacterial cells are able to respond to specific single acoustic frequencies and are capable of emitting sounds [65].…”
Section: Series XIImentioning
confidence: 99%
“…Several studies have suggested that the response to sound stimulation is complex, further confirming that cell types other than auditory cells can react directly to sound stimuli. For example, it has been shown that sound wave stimulation brings about significant changes to the protein structure of tobacco cells, producing an increase in the alpha helix structure and a decrease in the unwound β helix [62]; furthermore, sound stimulation has produced effects on the cell cycle and on the growth of plants [63,64]. It has been demonstrated that bacterial cells are able to respond to specific single acoustic frequencies and are capable of emitting sounds [65].…”
Section: Series XIImentioning
confidence: 99%